1998
DOI: 10.1016/s0014-5793(98)00915-6
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage populations of different origins have distinct susceptibilities to lipid peroxidation induced by β‐haematin (malaria pigment)

Abstract: We investigated the susceptibility of peritoneal mouse macrophages and macrophage and microglia cell lines to the peroxidative activity of [~-haematin, the synthetic polymer identical to native malaria pigment. The extent of lipid peroxidation, measured as production of thiobarbituric acid reactive substances (TBARS), was greater for peritoneal macrophages than for cell lines and microglia cells. TBARS production apparently was not attributable to the release of free iron from the protoporphyrin moiety, but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Although we cannot rule out the possibility that the increased HO-1 expression may be a direct effect of the heme moiety of BH, the results presented in Figure 2, along with the finding that the effect of BH on nitrite production was prevented by reducing agents, suggest that HO-1 up-regulation is caused by BH-induced oxidative injury. This conclusion is in agreement with the increased levels of lipid peroxidation induced by malaria pigment in human monocytes (Arese and Schwarzer, 1997) and mouse macrophages (Omodeo-Salè et al, 1998). In view of these considerations, it is difficult to reconcile our results with recent reports of the lack of induction of HO-1 in hemozoin-fed human monocytes (Schwarzer et al, 1999) that had been shown to experience oxidative stress upon ingestion of hemozoin (Schwarzer et al, 1992).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Although we cannot rule out the possibility that the increased HO-1 expression may be a direct effect of the heme moiety of BH, the results presented in Figure 2, along with the finding that the effect of BH on nitrite production was prevented by reducing agents, suggest that HO-1 up-regulation is caused by BH-induced oxidative injury. This conclusion is in agreement with the increased levels of lipid peroxidation induced by malaria pigment in human monocytes (Arese and Schwarzer, 1997) and mouse macrophages (Omodeo-Salè et al, 1998). In view of these considerations, it is difficult to reconcile our results with recent reports of the lack of induction of HO-1 in hemozoin-fed human monocytes (Schwarzer et al, 1999) that had been shown to experience oxidative stress upon ingestion of hemozoin (Schwarzer et al, 1992).…”
Section: Discussionsupporting
confidence: 76%
“…Because the two cell types ingested BH to a similar extent (Taramelli et al, 1995), the lower response to oxidant stress cannot be attributed to a different accumulation of pigment and is likely to depend on the cell's antioxidant status. In fact, BV2 cells have a lower content of unsaturated membrane fatty acids and higher levels of reduced glutathione (GSH) levels, both indicative of reduced sensitivity to oxidant stress (Omodeo-Salè et al, 1998). …”
mentioning
confidence: 99%
“…Even hemozoin that is considered a nontoxic storage of heme for the parasites has been shown to catalyze peroxidative processes in cell culture and cell-free systems. 10,11,51 Parasites seem to use different tools to cope with such an environment: (1) they are rich in antioxidant enzymes either imported from host or newly synthesized; (2) as shown here, the composition of their membranes is quite resistant to oxidative damage; and (3) to minimize contact with oxygen, they have evolved a way to survive in microaerophilic conditions. The food vacuole, the organelle where the digestion of hemoglobin occurs, is likely to be an anaerobic compartment, as we recently suggested.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that a better knowledge of the lipid composition of trophozoites membranes would help in solving the paradox of parasites, which grow in an iron-porphyrin rich environment, accumulating hemozoin that is toxic for host membranes 10,11 and yet survive.…”
Section: Introductionmentioning
confidence: 99%
“…A murine macrophage-like cell line (J774) [20] was maintained in MEM (Gibco-BRL-Life technologies) supplemented with 10% heatinactivated FBS (HyClone), 1% glutammine, 1% non-essential amino acid, 2% tricine and 1% penicillin-streptomycin in 5% at 37°C. J774 CO2 macrophages were mechanically collected with a cell lifter (Costar Italia, Milan, Italy) and transferred to a fresh medium every 3± 4 days.…”
Section: J774 Cellsmentioning
confidence: 99%